Examining neural correlates of skill acquisition in a complex videogame training program - Prakash, Ruchika S.; De Leon, Angeline A.; Mourany, Lyla; Lee, Hyunkyu; Voss, Michelle W.; Boot, Walter R.; Basak, Chandramallika; Fabiani, Monica; Gratton, Gabriele; Kramer, Arthur F. (Frontiers in Human Neuroscience, 2012)
Acquisition of complex skills is a universal feature of human behavior that has been conceptualized as a process that starts with intense resource dependency, requires effortful cognitive control, and ends in relative automaticity on the multi-faceted task. The present study examined the effects of different theoretically-based training strategies on cortical recruitment during acquisition of complex videogame skills. Seventy-five participants were recruited and assigned to one of three training groups: Fixed Emphasis Training (FET), in which participants practiced the game, Hybrid Variable Priority Training (HVT), in which participants practiced using a combination of part-task training and variable priority training, or a Control group that received limited game play. After 30 hours of training, game data indicated a significant advantage for the two training groups relative to the control group. The HVT group demonstrated enhanced benefits of training, as indexed by an improvement in overall game score and a reduction in cortical recruitment post-training. Specifically, while both groups demonstrated a significant reduction of activation in attentional control areas, namely the right middle frontal gyrus, right superior frontal gyrus, and the ventral medial prefrontal cortex, participants in the control group continued to engage these areas post-training, suggesting a sustained reliance on attentional regions during challenging task demands. The HVT group showed a further reduction in neural resources post-training compared to the FET group in these cognitive control regions, along with reduced activation in the motor and sensory cortices and the posteromedial cortex. Findings suggest that training, specifically one that emphasizes cognitive flexibility can reduce the attentional demands of a complex cognitive task, along with reduced reliance on the motor network.